The effect of enflurane and isoflurane on urea and creatinine clearences - Erhan, O.L.; Yildirim, A.M.; Arslan, I.N.; Ucar, O. (My University, 1990)
[Abstract Not Available]
Keywords: creatinine; enflurane; isoflurane; urea; article; clinical article; creatinine clearance; human; inhalation anesthesia; kidney function